Financial analysis with Microsoft Excel - Mayes, Timothy R. (Thomson/South Western, 2007)
Start mastering the tool that finance professionals depend upon every day. FINANCIAL ANALYSIS WITH MICROSOFT ® EXCEL covers all the topics you'll see in a corporate finance course: financial statements, budgets, the Market Security Line, pro forma statements, cost of capital, equities, and debt. Plus, it's easy-to-read and full of study tools that will help you succeed in class